Buster and the giant pumpkin - Brown, Marc Tolon (Boston, MA : Little, Brown and Co., 2005)
Buster sends postcards to his friends back home when he goes to Oregon and learns about pumpkins.
Accelerated Reader AR
Keywords: Pumpkin -- Fiction; Rabbits -- Fiction; Postcards -- Fiction; Seatte (Wash.) -- Fiction